Temperatura y germinación de las semillas de Dalbergia retusa (Papilionaceae), árbol en peligro de extinción - García, Elmer G (Universidad de Costa Rica, 2000)
The effec! of ternperature over Dalbergia retusa Hernsl. germination was studied in the laboratory. Seeds were disinfected and placed in Petri dishes for germination at 15, 20, 25, 30, 35, 40, and 45 oc. Germination percentage and the hypocotyl-radicle length were rneasured after three and five days. The highest germinatíon (85.6%) was obtaíned at 30 oc. Lower temperatures did no! favor germination. Sorne seeds were able lo germinate at 40 and 45 oC, a physiological adaptation to hol environrnents.